Respuesta :

♥Bonjour dear♥

Your answer is=>

[tex] { \bold{ = > y - 3 = \frac{1}{2} (x + 6)}}[/tex]

[tex]{ \bold{ = > y - 3 = \frac{1x}{2} + \frac{6}{2} }}[/tex]

[tex]{ \bold{ = > y - 3 = \frac{1x}{2} + 3 }}[/tex]

[tex]{ \bold{ = > y = \frac{1x}{2} + 3 + 3}}[/tex]

[tex]{ \bold{ = > y = \frac{1x}{2} + 6 }}[/tex]

✌Do mark my answer as brainliest ✌ ♥And follow me♥

Answer:

The first one is in standard form and is equivalent to the given equation.

Step-by-step explanation:

Standard form of a line is ax+by=c.

There is only one choice like that so I hope they are equivalent.

Let's check:

[tex]y-3=\frac{1}{2}(x+6)[/tex]

To clear the fraction multiply both sides by 2:

[tex]2y-6=1(x+6)[/tex]

[tex]2y-6=x+6[/tex]

Add 6 on both sides:

[tex]2y=x+12[/tex]

Subtract x on both sides:

[tex]-x+2y=12[/tex]

Multiply both sides by -1:

[tex]x-2y=-12[/tex]

They are!